Stochastic Modelling by Combining a Random Contraction and a Random Dilation for Decision Making - Artikis, Constantinos T.; Artikis, Panagiotis T. (Communications in Mathematics and Applications, 2024)
Random contractions and dilations of positive variables are essential probabilistic tools in the discipline of stochastic modelling. The present paper establishes two stochastic models that are formulated via the combination of the random contraction of a random variable with the random dilation of random variable. The theoretical contribution is based on the computation of the corresponding characteristic function, while the practical contribution is attained through the application of the proposed stochastic models in decision making within the field of financial management and risk management.
Keywords: Stochastic model; Contraction; Dilation; Characteristic function; Decision making